Design of a Server Application for Web-Based Automation of Darul Qur'an Student Registration - Maryam, Ridha Dewi; Qurratul Aini; Tsamratul Jannah; A. Hamdani (Yayasan Kita Menulis, 2026)
Study This discuss design server aplication for help automation of the registration process students at Darul Qur’an through a web-based platform. The systemThis developed for increase speed procesissing, accuracy record keeping and neatness previous data management handled manually. Stages study covering requirements analysis, system architecture design, and implementation using web technology. The design result show that the aplication is capable of handling registration in a structured manner, storing data centrally, and offering an easy-to-use interface. This system is expected to improve administrative efficiency and serve as a basis for developing additional features in the next phase.